(untitled) (Journal of Enam Medical College, 2025)
Background: Knowledge about diameters of head of the femur is necessary in order to reduce the risk of complications associated with surgical procedures performed in the area of hip joint due to vascular, metabolic or trauma causes, and to achieve an alignment of prosthesis to be implanted. This comprehensive studies and standardization of data for a study population have great importance, not only for anatomists and forensic experts but also for the determination of risk factors in pathological conditions (like osteoporosis, fractures etc), for preoperative planning and design of components of prostheses which may be used by the orthopedic surgeons in femoral head replacement surgery. Objectives: To construct the baseline data on different diameters of the fully ossified femoral head, determine any significant differences between the right and left femur and correlate with the previous study. The aim of the study is to record morphometric measurement that can throw further light on the existing data. Materials and Methods: This cross-sectional, descriptive type of study was conducted in Department of Anatomy, Mymensingh Medical College, Mymensingh from January 2019 to December 2019 on 150 dry fully ossified femurs of both sides with unknown sex. Data were statistically analyzed by using SPSS software, version 27.0. The diameters of head of the femur were measured by digital slide caliper. Results: The means (±SD) of vertical diameters of head of right and left femurs were 39.59 (±3.49) mm and 39.31 (±3.59) mm, of transverse diameters of head of right and left femurs were 36.32 (±3.79) mm and 34.81 (±3.06) mm and antero-posterior vertical diameters of head of right and left femurs were 41.15 (±3.18) mm and 41.20 (±3.44) mm respectively. Conclusion: There is no statistically significant differences between the right and left femoral diameters. J Enam Med Col 2022; 12(3): 132−136